Evaluating digital marketing as a tool for moonlighting among public servants in Nigeria - Salau, Abdulazeez; Brimah, Aminu Nassir; Akanbi, Kamoru Lanre; Ismaila, Yusuf; Abolade, Paul Ayobami (Indonesian Journal of Multidisciplinary Science, 2024)
The Nigerian economic situation has affected the people’s job preferences badly, and this situation necessitated their engagement in the moonlighting practice. Despite efforts by the government to alleviate poverty, which is ravaging the people, it is becoming alarming that individuals who are earning decent income have embraced moonlighting. The study examined the effect of small and medium enterprises moonlighting on the service delivery of employees in Kwara State public service. A survey research design was used, while the target population is 844, from which a sample size of 271 was obtained through the Taro Yamane (1967) formula. A multistage sampling technique was adopted, and a primary source was used to collect data with the aid of a well-structured questionnaire measured on a five-point Likert scale that consists of five items. Data were analyzed using the generalized linear model (GLM) and the business predictive model (BPM). On the basis of the individual statistical significance of the variables as indicated by the p-values in the model, all dimensions of SMEs passed their test of significance at 5% levels with respect to the task accomplishment (p<0.05) and service delivery (p<0.05) of employees involved in SMEs moonlighting. Thus, efficiency is greatly lost for moonlighters engaged in small and medium enterprises. About 44.8% reduction in task accomplishment (?=0.448, t0.05>1.96). The study concluded that moonlighters who engaged in SMEs activities impacted significant improvements in employee efficiency.